ANALISIS IMPLEMENTASI KURIKULUM ISMUBA (ISLAM, MUHAMMADIYAH DAN BAHASA ARAB) DI MUHAMMADIYAH BOARDING SCHOOL (MBS) PALOPO - Pribadi, Imam imam (Atta'dib Jurnal Pendidikan Agama Islam, 2025)
This study explores the implementation of the ISMUBA curriculum (Al-Islam, Kemuhammadiyahan, and Arabic Language) at Muhammadiyah Boarding School (MBS) Palopo, Indonesia. The research aims to analyze how this curriculum integrates Islamic values and character education within a boarding school system. Employing a qualitative descriptive approach with a phenomenological method, data were collected through in-depth interviews, observation, and documentation. The subjects included curriculum planners, ISMUBA teachers, and school administrators. Data were analyzed using the Miles and Huberman interactive model, including data reduction, display, and conclusion drawing, with validity ensured through source and method triangulation. The findings reveal that the ISMUBA curriculum at MBS Palopo is implemented regularly and contextually through well-planned integration of theological, pedagogical, and contextual dimensions. Formal learning in classrooms is extended into non-formal character development programs such as religious mentoring, tahfidz, halaqah, and Islamic practices embedded in students' daily routines. The collaboration between teachers and dormitory supervisors reinforces the internalization of Islamic values, resulting in increased student discipline, spiritual awareness, and moral conduct. Evaluation mechanisms involve regular teacher coordination, behavioral observation, and student character monitoring, ensuring responsiveness to student needs. The study concludes that the ISMUBA curriculum at MBS Palopo serves as a central framework for character education, blending religious instruction with academic learning in a boarding school context. These findings contribute to the discourse on integrated Islamic education and provide a model for character-based curriculum implementation in Islamic boarding schools.Â